1996
DOI: 10.1161/01.atv.16.12.1473
|View full text |Cite
|
Sign up to set email alerts
|

Esterified Estrogens With and Without Methyltestosterone Decrease Arterial LDL Metabolism in Cynomolgus Monkeys

Abstract: Although both epidemiological and experimental evidence suggests that estrogen replacement therapy reduces the risk of coronary heart disease, the mechanisms for this beneficial effect are largely unknown. Furthermore, the addition of progestins or androgens to estrogen replacement therapy is of concern. The objective of this study was to examine the effects of esterified estrogens alone or in combination with an androgen on arterial LDL metabolism and early atherogenesis in ovariectomized female cynomolgus mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…The protective effects of estradiol on the endothelium have been documented in hypercholesterolemic pigs and rabbits [22,23]. Others have reported that absence of estradiol induced by gonadectomy causes endothelial dysfunction in monkeys [24]. Our previous work showed that in vitro, 17h-estradiol attenuated inhibition of vasodilator responses to acetylcholine by ox-LDL or lysophosphatidylcholine in the isolated rabbit thoracic aortas [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effects of estradiol on the endothelium have been documented in hypercholesterolemic pigs and rabbits [22,23]. Others have reported that absence of estradiol induced by gonadectomy causes endothelial dysfunction in monkeys [24]. Our previous work showed that in vitro, 17h-estradiol attenuated inhibition of vasodilator responses to acetylcholine by ox-LDL or lysophosphatidylcholine in the isolated rabbit thoracic aortas [2].…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol has a biochemical structure similar to a-tocopherol and is a natural antioxidant [38]. It has been reported that estrogen replacement therapy decreases arterial LDL metabolism in cynomolgus monkeys [24]. In cultured endothelial cells, estradiol has been shown to inhibit oxidative modification of LDL [39].…”
Section: Discussionmentioning
confidence: 99%
“…5 To counteract oxidant stress effects on LDL and/or the artery wall, a number of potential antioxidants have been examined. In particular, some estrogens (eg, 17␤-estradiol) are known to reduce LDL accumulation in the artery wall 19,20 and to be potent antioxidants. [21][22][23] In addition, estrogens may protect endothelial cells from oxidative damage.…”
mentioning
confidence: 99%
“…The reaction mixture was incubated overnight at 4 • C and the labeled protein was purified by gel filtration on Sephadex G-25 M. The europium labeled antibody was eluted with 50 mM Tris-HCl buffer (pH 7.5) and stored at 4 • C until use [19,20].…”
Section: Europium Labeled Reagentsmentioning
confidence: 99%
“…RNA was extracted from cultured VSMC and was subjected to reverse transcription as previously described [19,20]. For ER(, we used 5 l of cDNA in the reaction mixture with the primers 5 -AA-TTCTGACAATCGACGCCAG-3 (forward) and 5 -GTGCTTCAACATTCT-CCCTCCTC-3 (reverse), for 30 cycles at 94 • C for 30 s, at 57 • C for 30 s and at 72 • C for 1 min.…”
Section: Expression Of Mrna Of Er˛and Erˇby Real Time Pcr In Vascularmentioning
confidence: 99%